CD8+ T-Cell–Derived Tumor Necrosis Factor Can Induce Tissue Factor Expression on Monocytes. (29th January 2019) - Freeman, Michael L; Panigrahi, Soumya; Chen, Bonnie; Juchnowski, Steven; Sieg, Scott F; Lederman, Michael M; Funderburg, Nicholas T; Zidar, David A
Abstract: Circulating CD8 + T cells and monocytes are activated during human immunodeficiency virus (HIV) infection and colocalize in the aortas of simian immunodeficiency virus–infected nonhuman primates. We hypothesized that CD8 + T cells could exert a proatherosclerotic effect via paracrine actions on monocytes. We found that T-cell receptor–stimulated CD8 + T cells induce monocytes to express tissue factor, a potent activator of coagulation. Tumor necrosis factor was both necessary and sufficient for this effect. Abstract : Activated CD8 + T cells can induce monocytes to express the coagulation element tissue factor (TF) in a tumor necrosis factor–dependent manner. Our data identify a possible mechanism for increased TF expression by monocytes during human immunodeficiency virus infection.